ABOUT ORGANIZATION OF INDEPENDENT WORK STUDENTS OF THE CORRESPONDENCE FORM OF EDUCATION (Pedagogy of Higher and Secondary Education, 2007)
The article discusses the aspects of organization of independent work of external students in Brest State university named after A.S. Pushkin, extending of its kind and optimization of its content.